Farmers’ perception in oil palm mechanization in FELDA Keratong, Pahang / Nur Munirah Mohd Azmi - Mohd Azmi, Nur Munirah (Faculty of Plantation and Agrotechnology, 2018)
The difficulties of farmers to apply the usage of mechanization have become one of the problematic situations for them in Malaysia oil palm fields due to several factors. As for the settlers in FELDA Keratong, the major difficulties that makes them hardly to apply mechanization usage is age factor, education background and the slope of the land which most of them are heavy undulating area with the elevation of 5 to 15 . A survey was conducted to identify the factors that affect the settlers’ current satisfaction with oil palm machines in the field. A group of settlers with a total of 217 respondents in both FELDA Keratong 8 and 10 was chosen as the sample for this survey. They have been asked to answer items of questionnaire and personal interview. A five point Likert scale analysis was use to scale the responses then the data was analyze by using Statistical Package for Social Science (SPSS) version 20 software. The usage of mechanization is hardly being applied due to the age and educational level factor where 32.4% from the age of 55 to 64 years old in Keratong 8 and 43.1% in Keratong 10 which are the highest number where most of them has a low exposure about the modern agriculture technology. These findings can actually help to improving the knowledge of farm machinery management to achieve a better satisfactory of farmers.